A comparative study of assessing organic matter decomposition between composting and vermicomposting process (Asian Journal of Medical and Biological Research, 2021)
The aim of the study was to compare the efficiency of organic matter degradation between composting and vermicomposting as well as the possibility of making compost and vermicompost using cattle manure. The experiment was conducted with two treatments, where one was conventional composting (T1) and another was vermicomposting (T2) from cattle manure. The sample from composted materials was collected at 0, 20, 40 and 60th day of experiment. Parameter studied were dry matter (DM), crude fiber (CF), crude protein (CP), ether extract (EE), ash content of the samples as well as pH and temperature change during the experimental period. Results found that a significant higher DM (P